Gastrointestinal syndromes preceding a diagnosis of Parkinson’s disease: testing Braak’s hypothesis using a nationwide database for comparison with Alzheimer’s disease and cerebrovascular diseases - Konings, Bo; Villatoro, Luisa; Van den Eynde, Jef; Barahona, Guillermo; Burns, Robert; McKnight, Megan; Hui, Ken; Yenokyan, Gayane; Tack, Jan; Pasricha, Pankaj Jay (Gut, 2023)
ObjectiveBraak’s hypothesis states that Parkinson’s disease (PD) originates in the gastrointestinal (GI) tract, and similar associations have been established for Alzheimer’s disease (AD) and cerebrovascular diseases (CVD). We aimed to determine the incidence of GI syndromes and interventions preceding PD compared with negative controls (NCs), AD and CVD.DesignWe performed a combined case-control and cohort study using TriNetX, a US based nationwide medical record network. Firstly, we compared subjects with new onset idiopathic PD with matched NCs and patients with contemporary diagnoses of AD and CVD, to investigate preceding GI syndromes, appendectomy and vagotomy. Secondly, we compared cohorts with these exposures to matched NCs for the development of PD, AD and CVD within 5 years.ResultsWe identified 24 624 PD patients in the case-control analysis and matched 18 cohorts with each exposure to their NCs. Gastroparesis, dysphagia, irritable bowel syndrome (IBS) without diarrhoea and constipation showed specific associations with PD (vs NCs, AD and CVD) in both the case-control (odds ratios (ORs) vs NCs 4.64, 3.58, 3.53 and 3.32, respectively, all p<0.0001) and cohort analyses (relative risks (RRs) vs NCs 2.43, 2.27, 1.17 and 2.38, respectively, all p<0.05). While functional dyspepsia, IBS with diarrhoea, diarrhoea and faecal incontinence were not PD specific, IBS with constipation and intestinal pseudo-obstruction showed PD specificity in the case-control (OR 4.11) and cohort analysis (RR 1.84), respectively. Appendectomy decreased the risk of PD in the cohort analysis (RR 0.48). Neither inflammatory bowel disease nor vagotomy were associated with PD.ConclusionDysphagia, gastroparesis, IBS without diarrhoea and constipation might specifically predict Parkinson’s disease.